Assessing interstate racial and socioeconomic disparities in newborn screening policies in the United States - Bedford, Shanaya; Vachuska, Karl (Frontiers in Public Health, 2024)
Introduction This paper explores racial and socioeconomic disparities in newborn screening (NBS) policies across the United States. While inter-state inequality in healthcare policies is often considered a meaningful source of systemic inequity in healthcare outcomes, to the best of our knowledge, no research has explored racial and socioeconomic disparities in newborn screening policies based on state of residence. Methods We investigate these disparities by calculating weighted average exposure to specific NBS tests by racial and socioeconomic group. We additionally estimate count models of the number (and type) of NBS conditions screened for by state racial and socioeconomic composition. Results Adding to the knowledge base that social determinants of health and health disparities are linked, our analysis surprisingly reveals little evidence of substantial inter-state inequity in newborn screenings along racial and socioeconomic lines. Discussion While there is substantial nationwide racial and socioeconomic inequity in terms of infant health, the distribution of state-level policies does not appear to be structured in a manner to be a driver of these disparities. Our findings suggest that efforts to reduce inequities in outcomes related to NBS should shift focus toward the delivery of screening results and follow-up care as discussion builds on expanding NBS to include more conditions and genomic testing.